Quality of life in people with spinal cordinjury - Angulo, Santiago M.; Reales, José M.; Sandín, Bonifacio; Santed, Miguel A. (Revista de Psicopatología y Psicología Clínica, 2019)
Abstract: The aim of this study was to examine the quality of life of people with spinal cord injury (SCI). A sample of 105 individuals with SCI completed a set of questionnaires to assess quality of life, daily stress, somatic symptoms, social support, and hardiness. Based on multiple regression analysis, we found that the quality of life of the participants was negatively associated with the severity of SCI (the most severity type [quadriplegia] showed the lowest quality of life), as well as with worse physical health and with an increase in weekly analgesic consumption. Conversely, there was a positive association between quality of life and hardiness, social support from friends, and a home adapted to spinal cord injury. Results suggest that people with a spinal cord injury have a lifestyle quite different from that of the rest of population, and their quality of life will be significantly diminished. Also, results show that the more complete and severe the SCI, the worse quality of life. Keywords: Quality of life; spinal cord injury; daily stress; well-being; health. Resumen: Calidad de vida en las personas con una lesión medular espinal. El objetivo del presente estudio consistió en examinar la calidad de vida en personas que sufren de lesión medular espinal (LME). Se aplicó un conjunto de cuestionarios a una muestra de 105 personas con LME con objeto de evaluar la calidad de vida, el estrés diario, la sintomatología somática, el apoyo social y el hardiness. Basándonos en análisis de regresión múltiple, encontramos que la calidad de vida de los participantes se asociaba negativamente con la gravedad de la LME (el tipo más grave [tetraplejia] presentaba la menor calidad de vida), así como también con peor salud física y con un incremento en el consumo semanal de analgésicos. Por el contrario, constatamos una relación positiva entre calidad de vida y hardiness, apoyo social de amigos y adaptación de la vivienda a su LME. Los resultados sugieren que las personas con LME presentan un estilo de vida distinto al del resto de la población, estando marcadamente reducida su calidad de vida. Así mismo, los resultados muestran que cuanto más grave sea la LME, más deteriorada está la calidad de vida de estas personas. Palabras clave: Calidad de vida; lesión medular espinal; estrés diario; bienestar; salud.